Policy Choices and Challenges in Expanding Access to Finance for Growth in Rural Nigeria - Akinlo, Anthony E. (European Journal of Sustainable Development, 2014)
Nigerian financial system has witnessed significant growth over the years. The phenomenal growth and high financial depth can be attributed in part to the country’s vast network of financial institutions, including rural finance. Improvements in rural finance notwithstanding, the supply of formal finance appears to be biased against the rural population. Rural communities remain centre of deprivations inspite of the various efforts at increasing financial services to them by the Government and the CBN. This therefore raises the following questions: what are the constraints and challenges of providing financial services in the rural areas? What are the policy initiatives that can be introduced to improve rural financial services in Nigeria? Hence the main objective of the paper is to examine the challenges and ways to improve rural financial services in Nigeria. Keywords: rural finance, growth, infrastructure, microfinance institutions.